Selected Uterine Immune Events Associated With the Establishment of Pregnancy in the Dog - Tavares Pereira, Miguel; Nowaczyk, Renata; Payan-Carreira, Rita; Miranda, Sonia; Aslan, Selim; Kaya, Duygu; Kowalewski, Mariusz P. (Frontiers in Veterinary Science, 2021)
In the dog, implantation takes place at approximately 17 days of embryonal life and, while exposed to relatively high circulating progesterone concentrations, embryos presence is required for the formation of decidua. Furthermore, a balance between pro- and anti-inflammatory responses in conceptus-maternal communication is crucial for the onset of pregnancy. Strikingly, the understanding of such immune mechanisms in canine reproduction is still elusive. Here, canine uterine samples from pre-implantation (day 10-12, E+) and corresponding non-pregnant controls (E-), implantation (day 17, Imp) and post-implantation (day 18-25, Post-Imp) stages of pregnancy were used to investigate the expression and localization of several immune-related factors. The most important findings indicate increased availability of CD4, MHCII, NCR1, IDO1, AIF1, CD25, CCR7 and IL6 in response to embryo presence (E+), while FoxP3 and CCL3 were more abundant in E- samples. Implantation was characterized by upregulated levels of FoxP3, IL12a, ENG and CDH1, whereas CD4, CCR7, IL8 and -10 were less represented. Following implantation, decreased transcript levels of TNFR1, MHCII, NCR1, TLR4, CD206, FoxP3 and IL12a were observed concomitantly with the highest expression of IL6 and IL1β. MHCII, CD86, CD206, CD163, TNFα, IDO1 and AIF1 were immunolocalized in macrophages, CD4 and Nkp46 in lymphocytes, and some signals of IDO1, AIF1 and TNF-receptors could also be identified in endothelial cells and/or uterine glands. Cumulatively, new insights regarding uterine immunity in the peri-implantation period are provided, with apparent moderated pro-inflammatory signals prevailing during pre-implantation, while implantation and early trophoblast invasion appear to be associated with immunomodulatory and rather anti-inflammatory conditions.